CLEANED eXtRa: model improvements - Technical report - Musau, Emmanuel Mwema (Bioversity International and the International Center for Tropical Agriculture, 2022)
The Alliance of Bioversity International and the International Center for Tropical Agriculture boasts itself as a center for agricultural research and innovation. The alliance has developed several tools to transform food systems and landscapes so that they can sustain the planet, drive prosperity, and nourish people in a climate crisis. CLEANED (Comprehensive Livestock Environmental Assessment for improved Nutrition, a secured Environment and sustainable Development along livestock value chain) is one of the decision-making tools in the intersection of livestock and environment. The tool is designed to work in data- scarce environments (Low- and middle-income developing countries) to quantify the environmental footprints of livestock systems and value chains along pathways of land and water requirements, soil health impacts, carbon sequestration, greenhouse gas emissions (GHGe) and a partial cost-benefit analysis to support decision-making.